Drought-related root morphological traits and non-structural carbohydrates in the seedlings of the alien Quercus rubra and the native Quercus robur: possible implication for invasiveness - Di Iorio, Antonino; Caspani, Anna Claudia; Beatrice, Peter; Montagnoli, Antonio (Frontiers in Forests and Global Change, 2024)
Quercus rubra L. is a moderately shade-tolerant tree species native to eastern North America, readily regenerating since its introduction in the Central and Southern European forests to displace the native pedunculate oak (Quercus robur). Under a scenario of increasing drought, understanding the seedling responses of these two species to water limitation is critical for forest conservation and management. To this aim, morphological, physiological and non-structural carbohydrates analyzes were performed on very-fine and fine roots of Q. robur and Q. rubra seedlings grown under controlled conditions and exposed to two levels of drought before allowing them to recover. Results show significant differences between species for all the investigated traits. The alien Q. rubra showed lower shoot and root biomasses than the native Q. robur, particularly for the thicker fine root 1–2 mm diameter class. However, both species equally invested more biomass in the shoot than the root system (R:S ratio <1). A significant response to drought was observed for the 0.5–1 mm fine root class, with moderate and severe droughted seedlings showing slightly higher biomass than control, particularly in Q. rubra. The overall growth reduction of Q. rubra suggests that the costs associated with the construction and maintenance outweigh the inputs from aboveground, as supported by the lower values of photochemical efficiency (Fv/Fm), quantum yield (ΦPSII) of PSII and stomatal conductance. In particular, the reduced stomatal conductance assured high midday leaf water potential (i.e., tissue hydration levels) at the expense of growth. The low starch concentration in Q. rubra’s very-fine roots correlated positively with the low photochemical efficiency under drought conditions, probably due to the reduction of photosynthate inputs from aboveground. In contrast to the anisohydric behavior reported, these outcomes highlight a rather isohydric behavior for Q. rubra, at least at the seedling stage and in the adopted experimental conditions, making this species highly competitive under the drier condition in the canopy openings during the summer period.